1989
DOI: 10.1126/science.2595371
|View full text |Cite
|
Sign up to set email alerts
|

A Model of Human Acute Lymphoblastic Leukemia in Immune-Deficient SCID Mice

Abstract: A human acute lymphoblastic leukemia (ALL) cell line that was transplanted into immune-deficient SCID mice proliferated in the hematopoietic tissues, invaded various organs, and led to the death of the mice. The distribution of leukemic cells in SCID mice was similar to the course of the disease in children. A-1 cells marked with a retrovirus vector showed clonal evolution after the transplant. SCID mice that were injected with bone marrow from three patients with non-T ALL had leukemic cells in their bone mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
103
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 229 publications
(105 citation statements)
references
References 33 publications
2
103
0
Order By: Relevance
“…Previous studies of human leukemias comparing Nude and SCID mice demonstrated the superiority of SCID mice in supporting the growth of BALL-1, Molt-4, CEM and A-1 human leukemia cell lines. 14,18,26 The results of these studies were very similar to those of the present investigations which showed the superiority of SCID over Nude mice in the growth of each of the cell lines examined.…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies of human leukemias comparing Nude and SCID mice demonstrated the superiority of SCID mice in supporting the growth of BALL-1, Molt-4, CEM and A-1 human leukemia cell lines. 14,18,26 The results of these studies were very similar to those of the present investigations which showed the superiority of SCID over Nude mice in the growth of each of the cell lines examined.…”
Section: Discussionsupporting
confidence: 87%
“…Experimental evidence for human CSCs is considered to be best established by demonstrating the ability of cells that are directly isolated from patients to produce malignant daughter populations in transplanted immunodeficient mice. This approach was pioneered with samples of cells from patients with various types of leukaemia (acute lymphoid leukaemia (ALL) 31 , acute myeloid leukaemia (AML) 32 and chronic myeloid leukaemia (CML) 33 ). Subsequently, the same approach has been successfully applied to solid tumours, including human cancers arising in the breast 34 , brain 14 , colon 16,35 , ovary 36 , lung 17 , and head and neck 37 .…”
Section: When a Clonal Hierarchy Is In Questionmentioning
confidence: 99%
“…To confirm our in vitro results in the human in vivo system, we used mice with severe combined immunodeficiency (SCID). Recent studies have demonstrated that the SCID mouse has several defects in both humoral and cellmediated immunity, and can serve as a recipient of grafts derived from a variety of human tissues, [22][23][24][25][26][27] including rheumatoid synovium. Thus, proliferative rheumatoid synovium can grow as a xenograft in SCID mice and pre- serve the histologic components of rheumatoid synovia.…”
Section: Figure 4 Immunohistochemical Analysis Of the Effects Of Hfasmentioning
confidence: 99%